DESAIN MEBEL DALAM PENDIDIKAN SENI DAN DESAIN - Wardani, Laksmi Kusuma (Institute of Research and Community Outreach - Petra Christian University, 2004)
Furniture design in art and design education use the thinking model which entangling design process with various problems which its character is not static and require the creative and critical opinion in joining creating energy, technological growth, and up to standard esthetics element to be produced. Problem solving which still on is going into effect in one case of furnitur design, differing at other case. The success of efficacy teaching and learning process in the studio of furniture design influenced by external and internal (study process, quality of human resource or lecturer and students, curriculum, education management, and also supporter facility learning and teaching process) factor. Abstract in Bahasa Indonesia : Desain mebel dalam pendidikan seni dan desain menggunakan model berfikir yang melibatkan proses desain dengan berbagai permasalahan yang sifatnya tidak statis dan membutuhkan pemikiran kritis dan kreatif dalam menggabungkan daya cipta, perkembangan teknologi, dan unsur estetika yang memenuhi syarat untuk diproduksi. Pemecahan masalah yang berlaku di satu kasus dalam desain mebel, berbeda pada kasus yang lain. Keberhasilan proses belajar mengajar di studio desain mebel dipengaruhi oleh faktor eksternal dan internal (proses pembelajaran, kualitas sumber daya manusia atau pendidik maupun peserta didik, kurikulum, manajemen pendidikan, maupun fasilitas-fasilitas penunjang proses belajar mengajar). Kata kunci : desain mebel, pendidikan, seni dan desain.